Multi-criteria analysis of climate change adaptation and socio-economic uncertainty strategies in drylands - Kertolli, Emirjona (2023)
On March 16 we held a workshop in Meknes, Morocco, this workshop was done under the ClimBeR initiative. The main objective was to identify the adaptation strategies that farmers in Saiss plain can implement in their farming systems in order to cope with climate change and socio-economic uncertainties and also to assess their feasibility by using a multicriteria analysis approach.